Postmodernism and customer centricity - Amirreza Mehraramolan (Journal of Marketing and Consumer Behaviour in Emerging Markets (JMCBEM), 2016)
There are many different explanations of customer centricity, and many people are in support of that concept whereas many others are against it. Different meanings can be found for customer centricity in literature. Which one could be the proper and most reliable one? Most of the views on customer centricity are based on foundational philosophical approaches and many different patterns are set as a guideline for the organizations which are willing to be customer-centric. In this paper, the aim is to look at the customer centricity phenomenon from the postmodernist point of view. The question of this study is linked to an anti-foundational philosophical approach (postmodernism) and it is shown how different the answers could be based on the philosophy approach that we choose. To collect the data, 10 in-depth interviews were done with senior business managers of customer-centric organizations in Iran. The results showed completely different answers from the postmodernist point of view.
Keywords: M10; L10; 650; postmodernism; positivism; customer centricity; phenomenology